Effects of breathing a hyperoxic gas mixture on perceptual, biochemical and performance recovery following simulated soccer match play - Daab, Wael; Rebai, Haithem; Abaïdia, Abd-Elbasset; Bouzid, Mohamed (Biology of Sport, 2025)
The aim of this study was to examine the effect of breathing a hyperoxic gas mixture on recovery kinetics after a simulated soccer match protocol. In a double-blind, randomized design, twenty-eight semiprofessional soccer players completed the Loughborough Intermittent Shuttle Test (LIST) followed by the administration of either a hyperoxic (FIO2 = 99.5%: HYP) or a normoxic gas mixture (FIO2 = 21%: NORM). HYP and NORM were administered immediately after LIST and daily for the next 3 days for 15 minutes. Physical performance (squat jump: SJ, countermovement jump: CMJ, maximal voluntary contraction: MVC, and 20 m sprint: SP), blood concentrations of muscle damage markers (creatine kinase: CK, lactate dehydrogenase: LDH), marker of inflammation (C-reactive protein: CRP) and Hooper index (HI) were assessed at baseline, 15 minutes and 24 h, 48 h and 72 h following the LIST. SJ, CMJ, MVC, and SP were lower at 15 min, 24 h, and 48 h in both conditions compared to the prior LIST (p < 0.05). However, the decrease in MVC was significantly attenuated at 15 min, 24 h and 48 h in HYP compared to the NORM condition (p < 0.01). Likewise, HI, muscle soreness and fatigue scores were significantly lower in HYP compared to the NORM condition up to 48 h following the LIST (p < 0.01). The present study suggests that the application of HYP immediately after a simulated soccer match and for the next 3 days promoted a lower fatigue-induced decrement in MVC and restored perceptual parameters of fatigue in semi-professional players.